Implementation Of Digital Signature On Banking - Hamdi, Nurul; Junidar, Junidar (Ubudiyah Indonesia University, 2016)
Abstract-one of the advantages of doing business in the internet world iscan he do trade transactions where and at any time, without the presenceof physical or face to face directly. In terms of profit in its own problemsarose, mainly related to authentication. Bagaimanapenj ual can restassured that the purchased product is the correct person or how the sellerknow that the credit card used the buyer is legitimate credit card hers. Theexample above is one of the problems in the internet world you can finishwith a digital signature. There are still many more problems in the internetthat can be solved with the use of a digital signature or digital signaturemisalnyadi the field of ecommerce, internet banking and more.Keyword:D igital Signatures, internet, e-commerce